En indledende undersøgelse af kapitalismens følelseshistorie - Matt, Susan; Kjærulff, Amalie (Slagmark - Tidsskrift for idéhistorie, 2020)
A Preliminary Exploration of the Inner History of Capitalism This chapter will examine an important transition in the history of emotions which illuminates how Americans came to embrace capitalistic feelings they once considered sinful. A central shift occurred when they stopped regarding their feelings as moral and cognitive traits and instead came to see them as neurological, non-volitional, physical impulses. When this occurred, once forbidden feelings became far less morally troubling. My history fits with a larger pattern that a number of historians of the emotions have traced. Their respective works have illustrated that during the late nineteenth and early twentieth centuries, a revolution in the descriptions and conceptions of inner life emerged in Europe and America.